MORPHOLOGICAL AND BIOMETRICAL OBSERVATIONS ON A STERNOPAGUS CONJOINED TWIN IN A BUFFALO (BUBALUS BUBALIS) - SINGH, PRAHLAD; GUPTA, KULDIP; SIDHU, S S; SINGH, OPINDER; SOOD, N K (The Indian Journal of Animal Reproduction, 2011)
An eight and a half year old multiparous Murrah buffalo cow weighing 500 kg presented with dystocia. Onpervaginum examination revealed a conjoined twin later diagnosed as sternopagus. The monster was deliveredpeNaginum after proper lubrication and obstetrical assistance. The detailed morphological and biometricat evaluationof the monster has been discussed.
Keywords: Monsters; Buffalo; Morphology; Biometry; Sternopagus twin; Conjoined monsters